2014
DOI: 10.1016/j.ijid.2014.04.015
|View full text |Cite
|
Sign up to set email alerts
|

The first case of bacteraemia due to non-O1/non-O139 Vibrio cholerae in a type 2 diabetes mellitus patient in mainland China

Abstract: Bacteraemia due to non-O1/non-O139 Vibrio cholerae is rarely documented in mainland China. We report such a case in a 70-year-old male with type 2 diabetes mellitus. The clinical features, phenotypic analyses, and presence of a panel of known virulence genes in the isolated strain are described. To the best of our knowledge, this is the first reported case of bacteraemia due to this strain in a T2DM patient without other coexisting underlying diseases in mainland China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 5 publications
1
12
1
1
Order By: Relevance
“…Further analysis of heterogeneity in three strains used by PFGE and MLST revealed different patterns among three strains. To our surprise, the MLST results demonstrated that two novel sequence types (ST518 and ST519) in our study were distinguished from the reported sporadic clone (Hao et al, 2015;Luo et al, 2013;Lu et al, 2014;Zhang et al, 2016) and the dominant clone of non-O1/non-O139 V. cholerae in China (ST80) (Luo et al, 2013). ST 519 has 2 single locus variants (SLVs) which were different from ST562 and ST268 in adk housekeeping gene.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Further analysis of heterogeneity in three strains used by PFGE and MLST revealed different patterns among three strains. To our surprise, the MLST results demonstrated that two novel sequence types (ST518 and ST519) in our study were distinguished from the reported sporadic clone (Hao et al, 2015;Luo et al, 2013;Lu et al, 2014;Zhang et al, 2016) and the dominant clone of non-O1/non-O139 V. cholerae in China (ST80) (Luo et al, 2013). ST 519 has 2 single locus variants (SLVs) which were different from ST562 and ST268 in adk housekeeping gene.…”
Section: Discussioncontrasting
confidence: 48%
“…Several genetic elements, including R plasmids, the class I integron and the SXT element, have been reported to be closely associated with the spread of genetic elements by mediating antibiotic resistance in V. cholerae (Pan et al, 2008;Dalsgaard et al, 2000;Hochhut et al, 2000). In contrast, most non-O1/non-O139 V. cholerae strains were sensitive to the third-generation cephalosporins, fluoroquinolones, piperacillin/tazobactam, tetracyclines, chloramphenicol according to the previous studies (Chowdhury et al, 2016;Hao et al, 2015;Lu et al, 2014). A few strains were resistant to third-generation cephalosporins because of carrying gene encoding extended-spectrum-lactamase (ESBL) (Ismail et al, 2013;Petroni et al, 2002).…”
Section: Discussionmentioning
confidence: 80%
“…In this study, antimicrobial agents recommended as first choice agents for the treatment of V. vulnificus and V. cholerae non-O1/non-O139 infections such as fluoroquinolones, tetracyclines, and extended spectrum cephalosporins were found to be effective in vitro against both species. However, the administration of aminopenicillins, carbapenems, or aminoglycosides for treatment of V. cholerae non-O1/non-O139 infections, which has been reported in few studies (Daniels and Shafaie, 2000 ; Feghali and Adib, 2011 ; Lu et al, 2014 ) should be considered carefully, as non-susceptibility was most frequently observed against ampicillin and streptomycin and sporadically to carbapenems. For V. vulnificus , non-susceptibility was exclusively observed to the aminoglycosides streptomycin and kanamycin.…”
Section: Discussionmentioning
confidence: 99%
“…Several case studies on V. cholerae non-O1/non-O139 bacteremia and wound infection exist, where fluoroquinolones and third-generation cephalosporins have been used (Huhulescu et al, 2007 ; Petsaris et al, 2010 ). But also treatment with ampicillin or last-line carbapenems has been described (Feghali and Adib, 2011 ; Lu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non-O1/non-O139 Vibrio cholerae are being recognized increasingly as invasive pathogens in bacteremia, particularly among patients in an immunosuppressed condition. 1 The presenting symptoms of bacteremia due to non-O1/non-O139 V. cholerae are well described. However, the genotype and phenotype of virulence factors that allow the strains to invade the bloodstream are not well elucidated.…”
Section: Introductionmentioning
confidence: 99%